EVALUATION OF FENUGREEK (TRIGONELLA FOENUM-GRAECUM L.) GERMPLASM UNDER SUBTROPICAL CLIMATE CONDITIONS OF FAISALABAD - IQBAL , M; RASHID , K; RASHID , K; HAMMAD , G; ALI, A; LATIF, A; AMIN, E; TAHIR, M; TAHIR, A; SHABBIR, RH; et al. (Biological and Clinical Sciences Research Journal, 2024)
Fenugreek (Trigonella foenum-graecum L.) commonly known as methi, is a self-pollinating, leguminous crop native to the subcontinent and the Eastern Mediterranean region. An experiment was conducted to evaluate nine genotypes in Faisalabad region during year 2022-23.The study highlighted significant variations among fenugreek genotypes, with MethiQasoori (Check) being the fastest to first cutting at 40.2 days. Other quick-maturing varieties included Fenu-06 and Fenu-05, while Fenu-07 and Fenu-02 took longer. For the second cutting, MethiQasoori also led at 70.2 days. Fenu-04 was the tallest at 90.1 cm and had the highest leaf yield of 23.62 T/Ha. EFG-1144A had the lowest yield at 7.88 T/Ha. Fenu-04 had the highest 1000 seed weight at 1.333 g, indicating potential for better seed quality. Yellow flowers found in Fenu-04, MethiQasoori, Fenu-02, Fenu-01, and EFG-1144A, indicating a preference or trend towards yellow flowers in several varieties. White flowers had been found in Fenu-06, Fenu-05, Fenu-03, and Fenu-07, suggesting that white flowers was less common. All varieties were vulnerable to aphids, emphasizing the need for pest management.